Anatomical structure of stem in the above- and underground portions of Rosa rugosa suckers - Fouda, R. (International Journal of Horticultural Science, 1999)
Comparitive histological studies were made on the underground and the aboveground stem parts of Rosa rugosa taken from one year old suckers. The underground stem parts were characterized with thicker primary cortex, phloem and pith, weaker phloem fibers, wider cambial zone, medullary rays, xylem and phloem rays as compared with the aboveground stem parts. The most marked differences in the underground stem parts were in the wide cambial zone and in the development of some adventitious roots.